Pendekatan Antropologi dalam Studi Agama - Feryani umi Rosidah (Religió: Jurnal Studi Agama-agama, 2011)
Religious phenomenon is a universal symptom, unique and full of mystery. Its existence was always traced from prehistoric until modern times. The fact that religious society has been confronted to a collective consciousness, structural adjustment and cultural understanding of religion is a must. Therefore, religion should not be placed in a subordinate position that associated with social, cultural, economic and politic development. This should be understood as an effort to look back the diversity of public religions. Various religious existences are studied and reviewed holistically with studying their function and relation to other cultural aspects. Religious existence symptoms were assessed with anthropological approach and its unity with other cultural aspects. Anthropology aims to appreciate symbols, norms and society prevailing systems. Religion is a cultural phenomenon. In other word, as a social science, anthropology does not discuss the “actual religion” or sacred dogma. The center of attention is human activity as a cultural phenomenon. This requirement can be interpreted as a response of religious society to the changes that occur rapidly. Religious studies through a more anthropological approach can describe the role of human / religious community in action, so that religion is defined as part of lives (culture) of individuals or groups, which each adherent has authority in understanding the religion and apply it.